Gjaldtaka af nýjum orkugjöfum í samgöngum - Ingvar Karlsson (2011)
The purpose of this project was to explore the influence of alternative energy in transportation in Iceland would have on government income from taxation on fossil fuel, and what taxation should be on new alternative energy so the government income will not be affected. In Iceland fossil fuels are the main fuels in transportation Worldwide the price of fossil fuels has increased hugely these last semesters. Recently there has been much discussion about replacing fossil fuels with alternative energy sources in transportation. This discussion is particularly driven by the negative effect the use of fossil fuels has on the environment, both locally as pollution and globally with the emission of greenhouse gasses. It is clear that the transportation sector is one of the main cause of greenhouse gas emissions. The environmental effect from transportation is both regional and worldwide, and most nations have in place or are making policies to reduce the emission of carbon dioxide and other greenhouse gasses as well as facilitate the use of alternative fuels to replace fossil fuels in transportation. The main conclusion of this project is that taxation of new resources in alternative energy in transportation is necessary to finance the transportation infrastructure in Iceland which is big and expensive. To motivate the change to alternative energy in transportation, it is a possible to increase temporarily the taxation on fossil fuels, but after a few years the taxation will have to get higher on the new alternative energy source to keep the government's income from transportation similar as before. The cost of the repair and management of the transportation infrastructure is based on how much it is used. Therefore there must be a connection between the cost and income of transportations. Keywords: Alternative energy, transport, taxation, cars, government income.